The soil resistome: a critical review on antibiotic resistance origins, ecology and dissemination potential in telluric bacteria. (17th December 2014) - Nesme, Joseph; Simonet, Pascal
Summary Soil is a large reservoir of microbial diversity and the majority of antimicrobial compounds used today in human and veterinary health care have been isolated from soil microorganisms. The Darwinian hypothesis of an 'arms‐shields race' between antibiotic producers and resistant strains is often cited to explain antibiotic resistance gene determinants (ARGD) origins and diversity. ARGD abundance and antibiotic molecule exposure are, however, not systematically linked, and many other factors can contribute to resistance gene emergence, selection and dissemination in the environment. Soil is a heterogeneous habitat and represents a broad spectrum of different ecological niches. Soil harbours a large genetic diversity at small spatial scale, favouring exchange of genetic materials by means of horizontal gene transfer (HGT) that will contribute to ARGD dissemination between bacteria and eventually acquisition by pathogen genomes, therefore threatening antibiotic therapies. Our current knowledge on the extent of the soil resistome abundance and diversity has been greatly enhanced since the metagenomic revolution and help of high‐throughput sequencing technologies. Different ecological hypotheses explaining their high prevalence in soil and questioning their transfer rate to pathogens, in respect to these recent experimental results, will be discussed in the present review.